Assembling, channeling, and orienting watershed management: The performative roles of computer models in environmental management institutions - Jeremy Trombley (Water Alternatives)
Large-scale watershed management increasingly depends on the use of computational models to inform decision-making and track management goals; however, the roles that models play in environmental management institutions far exceed their informational content. Science studies scholars have approached modelling as also a performative practice that shapes the relational context of watershed management. Drawing on an ethnographic approach, this article examines a single computer model as it is developed and deployed in an environmental management organisation. The study shows that a single model can serve multiple roles within a watershed management institution depending on specific conditions and contexts; further, by serving these multiple roles rather than a single informational one, models are uniquely useful for organising environmental science and management practices and institutions across a heterogeneous set of agents. Examining these multiple roles can help us to understand not only the process of computational modelling, but also the process of management and how different organisations can coordinate with one another through the use of modelling.